Progesterone Receptor Membrane Component 1 (PGRMC1) in cell division: its role in bovine granulosa cells mitosis (International Journal of Health, Animal Science and Food Safety, 2015)
The present studies were aimed to assess Progesterone Receptor Membrane Component-1 (PGRMC1) role in regulating bovine granulosa cells (bGC) mitosis. First, we performed immunofluorescence studies on in vitro cultured bGC collected from antral follicles, which showed that PGRMC1 localizes to the spindle apparatus in mitotic cells. Then, to evaluate PGRMC1 effect on cell proliferation we silenced its expression with RNA interference technique (RNAi). Quantitative RT-PCR and immunoblotting confirmed down-regulation of PGRMC1 expression, when compared to CTRL-RNAi treated bGC (p
Keywords: bovine granulosa cells; mitosis; PGRMC1